Zakat Profesi bagi Advokat menurut Hukum Positif Indonesia - Yahya Asmu’I (CV. Creative Tugu Pena, 2024)
The research examines and discusses professional zakat for advocates from the perspective of positive law in Indonesia, what are the provisions regarding nisab, haul and how to calculate them according to law, mui fatwa and other written legal regulations that are recognized and applicable in the Indonesian legal and regulatory system. This research is normative legal research using a statutory approach. The research data is in the form of qualitative data obtained using the method library research or literature, while analysis and conclusion-making techniques use analytical descriptive techniques. Based on the results of the discussion, the following conclusions can be drawn: 1. Professional zakat for advocates according to Indonesian positive law is obligatory for Muslims provided that the assets are fully owned, halal, and have sufficient nisab but haul provisions do not apply, 2. Nisab for professional zakat for advocates is worth 85 grams of gold and the zakat rate is 2.5%, 3. The method of payment of professional zakat for advocates can be issued when receiving fees from clients if the nishab is sufficient, or if it does not reach the nishab, then all income is collected for one year then zakat is issued if the net income is sufficient nishab. Keywords: Professional Zakat, Zakat Law, Advocate Zakat